Structure of the Inhibited Smooth Muscle Myosin and Its Implications on the Regulation of Insect Striated Muscle Myosin - Shaopeng Sun; Yi-Ning Lu; Xiang-dong Li (Life)
Class II myosin (myosin-2) is an actin-based motor protein found in nearly all eukaryotes. One critical question is how the motor function of myosin-2 is regulated. Vertebrate myosin-2 comprises non-muscle myosin, smooth muscle myosin and striated muscle myosin. Recent studies have shown that smooth muscle myosin, in its inhibited state, adopts a folded conformation in which the two heads interact with each other asymmetrically, and the tail is folded into three segments that wrap around the two heads. It has been proposed that the asymmetric head-to-head interaction is a conserved, fundamental structure essential for the regulation of all types of myosin-2. Nearly all insects have only a single striated muscle myosin heavy chain (MHC) gene, which produces all MHC isoforms through alternative splicing of mutually exclusive exons. Most of the alternative exon-encoded regions in insect MHC are located in the motor domain and are critical for generating isoform-specific contraction velocity and force production. However, it remains unclear whether these alternative exon-encoded regions participate in the regulation of insect striated muscle myosin. Here, we review the recently resolved structure of the inhibited state of smooth muscle myosin and discuss its implications on the regulation of insect striated muscle myosin. We propose that the alternative exon-encoded regions in insect MHC not only affect motor properties but also contribute to stabilizing the folded conformation and play a crucial role in regulating insect striated muscle myosin.